Budaya Pamali dan Strategi Penerapan Pola Asuh Berkesadaran - Indrayani, Rusmiati; Al-Mubarak, Ahmad Munir (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2024)
The purpose of this study is to describe the strategy of implementing conscious parenting in forming an understanding of taboo culture. This study uses a mixed method or a combination of quantitative and qualitative methods. The number of respondents/research informants is 100 people. The determination of respondents uses a purposive sampling technique. The results of the study, as many as 85% of the old generation of the Banjar tribe still believe in taboos and prohibitions as a form of local wisdom. The types of taboos are divided into three parts, customary taboos (60%), natural taboos (10%), and taboos in social interaction (20%). The strategy of inheriting values in the form of advice and examples is integrated through parenting. The combination of the application of authoritarian, authoritative, and laizs faire parenting patterns forms a conscious parenting pattern. As many as 75% of respondents acknowledge the important role of the older generation such as grandparents, fathers and mothers as guardians of cultural identity.